Mitogenomic analyses from ancient DNA - Paijmans, J.; Gilbert, Thomas; Hofreiter, M. (Academic Press, 2013)
The analysis of ancient DNA is playing an increasingly important role in conservation genetic, phylogenetic and population genetic analyses, as it allows incorporating extinct species into DNA sequence trees and adds time depth to population genetics studies. For many years, these types of DNA analyses (whether using modern or ancient DNA) were largely restricted to the analysis of short fragments of the mitochondrial genome. However, due to many technological advances during the past decade, a growing number of studies have explored the power of complete mitochondrial genome sequences (mitogenomes). Such studies were initially limited to analyses of extant organisms, but developments in both DNA sequencing technologies and general methodological aspects related to working with degraded DNA have resulted in complete mitogenomes becoming increasingly popular for ancient DNA studies as well. To date, at least 124 partially or fully assembled mitogenomes from more than 20 species have been obtained, and, given the rapid progress in sequencing technology, this number is likely to dramatically increase in the future. The increased information content offered by analysing full mitogenomes has yielded major progress with regard to both the phylogenetic positions of extinct species, as well as resolving population genetics questions in both extinct and extant species.